Nutritional Value Analysis of Dried Noodles with the Addition of Tuna (Thunnus sp.) and Skipjack (Katsuwonus Pelamis) - Tukan, Maria Magdalena Nona Motu; Dawan, Benediktus J. G. J.; Lida, Kristoforus Nama (LifeSciFi, 2025)
Dried noodles are a popular food in Indonesia, but their nutritional value is often limited due to high carbohydrate content. This study aimed to develop nutrient-rich dried noodles by adding tuna and skipjack fish, evaluating their sensory quality and nutritional composition to support healthier diets and food diversification. The research used a completely randomized design to compare noodles made with tuna and skipjack fish. Fifteen panelists assessed taste, color, aroma, and texture on a scale from poor to very good, while nutritional content, including moisture, ash, protein, fat, and carbohydrates, was analyzed using standard laboratory methods. Results showed that skipjack noodles had higher protein (18.324%) and mineral content (1.735%) than tuna noodles (14.193% protein, 1.535% mineral), with both rated good to very good for sensory qualities, especially skipjack for its vibrant color. However, moisture levels (22–25%) exceeded industry standards, suggesting shelf-life challenges. In conclusion, both noodle types offer enhanced nutrition and consumer appeal, with skipjack noodles being more protein-rich, making them a promising option for improving dietary protein intake, though better drying methods are needed for commercial viability.